THE IMPACT OF BUSINESS PROCESS MODELING AND NOTATION (BPMN) ON ACCOUNTING INFORMATION SYSTEM DESIGN: A CASE STUDY OF AN INDONESIAN VILLAGE-OWNED ENTERPRISE - Nabilla Lailatuz Zaidah; Nur Indah Riwajanti; Nurafni Eltivia (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze and design an AIS using the Business Process Model and Notation (BPMN) to improve the effectiveness and efficiency of BUMDes Pulotondo's financial reports. The approach used in this design is Research and Development using the ADDIE model. By analyzing and designing financial applications using BPMN, BUMDes Pulotondo is expected to be able to improve efficiency and transparency in its financial management. The results of the study show that the results of the analysis using the fishbone diagram can create an application design with two levels of system users, namely administrators and staff. Using BPMN shows the business process flow of financial reports, namely the Profit and Loss Report, Statement of Changes in Equity, Cash Flow Report, and Balance Sheet Report. This research provides an original contribution by integrating BPMN modeling with the ADDIE development framework to design an Accounting Information System (AIS) specifically designed for Village-Owned Enterprises (BUMDes). In contrast to previous studies that often apply generic financial systems, this study discusses the unique operational characteristics of BUMDes Pulotondo. The use of BPMN provides clear and standardized visualization of financial processes, while the implementation of user-level access (administrator and staff) increases the security and usability of the system.